(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2023)
This article discusses insights of a research regarding the platformed audiovisualities on the strategies by the female independent musicians of Porto Alegre (Brazil) and Milan (Italy) during the Covid-19 pandemic, considering their practices of resistance in this period with the usages an appropriation of technology. Based on qualitative research using the cartographic method (Canevacci, 1997), we mapped female musicians (composers, singers and instrumentalists), and their videos, and made interviews. Our analysis shows two relational tendencies, constellations (Canevacci, 1997), which illuminate the information gathered, making it possible to understand and analyse it by means of the empirical data connection and edition, in an interpretative process which holds the knowledge’s luminous sense: 1) the narrative built on the divulgation steps; and 2) the network articulated with the audience and other musicians. Considering their strategies, our research highlights the artivism which is present on their actions. With that, when actualising the audiovisualities, being women and into practices of resistance, they might have also actualised the do-it-yourself ethos in both independent music scenes.